Desenvolvimento de métodos para determinação de resíduos de trifenilestanho em água e solo por cromatografia líquida acoplada à espectrometria de massas em série - Santos, Gabriel Capeletto dos (2018)
Triphenyltin has been widely used as fungicide in several crops, but its use in irrigated rice crop was banned in Brazil because it poses a high risk to the environment. In this work, methods for determination of triphenyltin (TPhT) residues in water and soil samples by liquid chromatography with tandem mass spectrometry (LC-MS/MS) were developed and validated. For water analysis, solid phase extraction (SPE) was used to evaluate univariate variables such as: sample volume, sample pH, type and volume of elution solvent. For soil analysis, a complete design of experiments 23 was applied to the QuEChERS method to optimize sample preparation for soil evaluating variables such as partition, type and acid concentration in the extraction solvent. Practical methods limits of quantification (LOQ) were 0.1 μg L-1 and 10 μg kg-1 for water and soil samples, respectively. Satisfactory accuracy, with recoveries from 84 to 113% for water samples and 72 to 99% for soil samples, as well as good precision, with overall relative standard deviation (RSD) from 3 to 18% for water samples and 2 to 7% for soil samples were achieved. The validated methods were applied to real samples and no residues of TPhT were found. Although, the proposed methods presented adequate performance using standard addition procedure. Results indicated that proposed methods are suitable for routine analysis of TPhT residues in water and soil samples.